Sources and transport pathways of precipitating waters in cold-season Deep North Atlantic cyclones - Papritz, Lukas; id_orcid:0 000-0002-2047-9544; Aemisegger, Franziska; Wernli, Heini; id_orcid:0 000-0001-9674-4837 (Journal of the Atmospheric Sciences, 2021)
ISSN:0022-4928 ISSN:1520-0469